2017
DOI: 10.1063/1.4980125
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electromagnetic propagation in the magnetic plasma state in spin-ice systems

Abstract: Low energy excitation states in magnetic structures of the so-called spin-ices are produced via spin flips among contiguous tetrahedrons of their crystal structure. When there are sufficient free positive and negative charges, the system behaves as a magnetic plasma, which could correspond to the highest temperature peak of the specific heat. The electromagnetic waves in both unconfined and confined systems (waveguides) filled with materials of magnetic charges can be able to transmit information and energy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The flexibility in tuning constituting element's size, hence the inter-elemental dipolar interaction energy, in an artificial magnetic honeycomb lattice can be exploited to generate magnetic charge defects at high temperature. Previously, magnetic charge defect was shown to mediate electrical conduction in a spin ice material via the interaction between electron's spin, s , at the Fermi surface and the transverse local fluctuation in magnetic field B(k) due to the monopole dynamics ( Chern et al., 2013 ; Lopez-Bara and Lopez-Aguilar, 2017 ). According to the formulation, magnetic charge defect's relaxation time plays crucial role in temperature-dependent magnetic charge-mediated conduction, in addition to the residual purely electrical conduction.…”
Section: Introductionmentioning
confidence: 99%
“…The flexibility in tuning constituting element's size, hence the inter-elemental dipolar interaction energy, in an artificial magnetic honeycomb lattice can be exploited to generate magnetic charge defects at high temperature. Previously, magnetic charge defect was shown to mediate electrical conduction in a spin ice material via the interaction between electron's spin, s , at the Fermi surface and the transverse local fluctuation in magnetic field B(k) due to the monopole dynamics ( Chern et al., 2013 ; Lopez-Bara and Lopez-Aguilar, 2017 ). According to the formulation, magnetic charge defect's relaxation time plays crucial role in temperature-dependent magnetic charge-mediated conduction, in addition to the residual purely electrical conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Then, to evaluate the ponderomotive force (19) we make use of ( 13) and (17). Keeping ourselves in the slowly-varying regime…”
Section: Ponderomotive Force On Electrons Owed To the Presence Of Mag...mentioning
confidence: 99%
“…In addition to different experimental attempts to detect these particles (see e.g. [12][13][14]), several studies have shown the effect of hypothetical magnetic monopoles in different aspects of physics such as astrophysics [10,15], high energy physics [16,17], spin ice, [18][19][20][21] and plasma physics [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The values of the n 0 and m can be obtained from indirect experimental results arising from the magnetic conductivity (see refs 7,8 and references therein) they may be between 0.25 and 0.75 in the case without first order phase transition. The energies b and b′ are those energies which do not depend on the increasing of the probability of appearance of the magnetic charges due to the temperature evolution.…”
Section: Transition From the Dipolar State (9) Towards A Monopolar Plmentioning
confidence: 99%
“…The properties that present these modifications of their magnetic structures could have a double interest: on one hand, it could allow us to discover new characteristics for low-energy excitation states within the magnetic theory and on the other hand, could imply that these compounds were serious candidates for devices capable of propagating both information and energy 3,7,8 . The compounds of Holmium or Disprosium Dy 2 Ti 2 O 7 and Dy 2 Ti 2 O 7 , which crystallize in a pyrochlore type [refs 3,4 and references therein] present a magnetic structure whose main characteristic is that spin-flips in the magnetic moments of the lanthanide ions placed in the vertexes shared by contiguous tetrahedrons can progress in their crystal structures.…”
Section: Introductionmentioning
confidence: 99%